Defining the Pillars of Trade Union Freedoms: the Polish Example - Gołaś, Jakub (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2018)
The aim of the article is to present and characterise the essence of four fundamental pil-lars (the freedom of association, the self-governance, the independence and the equality) of trade union freedoms in the Polish legal system. The author presents such aspects as the classification of trade union freedoms or the characterisation of chosen specific union pillars. The article is based on the review of the relevant national legislation (in-cluding the Polish Constitution, international agreements and the Act on Trade of 23th May 1991), doctrine and judicature.